Ion beam induced 18F-radiofluorination: straightforward synthesis of gaseous radiotracers for the assessment of regional lung ventilation using positron emission tomography. Issue 80 (16th September 2016) - Gómez-Vallejo, V.; Lekuona, A.; Baz, Z.; Szczupak, B.; Cossío, U.; Llop, J.
Abstract : [ 18 F]CF4 and [ 18 F]SF6 are produced in a cyclotron target under proton irradiation. [ 18 F]CF4 is suitable for assessing lung ventilation. Abstract : A simple, straightforward and efficient method for the synthesis of [ 18 F]CF4 and [ 18 F]SF6 based on an ion beam-induced isotopic exchange reaction is presented. Positron emission tomography ventilation studies in rodents using [ 18 F]CF4 showed a uniform distribution of the radiofluorinated gas within the lungs and rapid elimination after discontinuation of the administration.